The Bonesetter's Daughter - Tan, Amy (London Flamingo, 2001)
Lu Ling Young is now in her eighties, and finally beginning to feel the effects of old age. Trying to hold on to the evaporating past, she begins to write down all that she can remember of her life as a girl in China. Her daughter Ruth moves in and discovers the story of her tumultuous life
Include Epilogue
Keywords: China -- Mothers and daughters -- Chinese American women